The National Curriculum Changes and Their Effects on English Language Teaching in Indonesia - Annisa; Siti Norfita Sari; Kalayo Hasibuan (English Education Study Program Faculty of Teacher Training and Education, 2025)
The objectives of this research are to explore the evolution and implications of curriculum reforms in English Language Teaching (ELT) in Indonesia, focusing on the challenges and opportunities these reforms present for educators and learners. This research is a qualitative study that examines the historical development of ELT curricula, pedagogical shifts, teacher and student adaptations, contextual challenges, and future recommendations. The sample of this research includes education policymakers, ELT educators, and students across different regions of Indonesia. The data were gathered by using interviews, surveys, and document analysis, and were analysed by employing thematic analysis to identify key trends and insights. The findings showed that while recent curriculum reforms have made significant strides in introducing competency-based learning, critical thinking, and digital literacy, they have also highlighted systemic challenges such as resource inequalities, regional disparities, and varying levels of teacher readiness. In conclusion, the research suggests that future curriculum reforms should focus on addressing these challenges through equitable resource distribution, enhancing teacher professional development, and adapting the curriculum to better meet the socio-cultural and linguistic diversity of Indonesia.